MANAJEMEN SISTEM PENELITIAN DI PONDOK PESANTREN DAAR EL-QOLAM TANGERANG BANTEN - FIRMANSYAH, FIRMANSYAH (PPs UNJ, 2016)
The purpose in this research is to obtain the discription of modern boarding school management as a sistem with socio-cultural basis in Daar el-Qolam Islamic Boarding School. This research is a qualitative research with case study using a sistem approach and using Miles and Huberman model including the data reduction, data display, conclusion, and verivication. Data collection for study was carried out by means of interviews and observation towards several respondents i.e principal, teachers, administrators, students, students parents, principal family, and the office of Ministery of Relegion. The result of this research showed that management sistem input represented in the profile. That Daar el-Qolam Boarding School is adaptist in profile. The process of management represented by dinamic, where as Daar el-Qolam Islamic Boarding School is multietnic in leadership pattern. The output of management sistem represented in graduates and publics apprecation. Where Daar el-Qolam Islamic Boarding School on their life skills. The environmental of management sistem represented in socio culture, where as Daar el-Qolam with multicultures has balance achievements between relegion and general field of study including language skills.